Diversity of functional alterations of the ClC‐5 exchanger in the region of the proton glutamate in patients with Dent disease 1. Issue 5 (1st March 2021) - Sakhi, Imène; Bignon, Yohan; Frachon, Nadia; Hureaux, Marguerite; Arévalo, Bárbara; González, Wendy; Vargas‐Poussou, Rosa; Lourdel, Stéphane
Abstract: Mutations in the CLCN5 gene encoding the 2Cl − /1H + exchanger ClC‐5 are associated with Dent disease 1, an inherited renal disorder characterized by low‐molecular‐weight (LMW) proteinuria and hypercalciuria. In the kidney, ClC‐5 is mostly localized in proximal tubule cells,  where it is thought to play a key role in the endocytosis of LMW proteins. Here, we investigated the consequences of eight previously reported pathogenic missense mutations of ClC‐5 surrounding the "proton glutamate" that serves as a crucial H + ‐binding site for the exchanger. A complete loss of function was observed for a group of mutants that were either retained in the endoplasmic reticulum of HEK293T cells or unstainable at plasma membrane due to proteasomal degradation. In contrast, the currents measured for the second group of mutations in Xenopus laevis oocytes were reduced. Molecular dynamics simulations performed on a ClC‐5 homology model demonstrated that such mutations might alter ClC‐5 protonation by interfering with the water pathway. Analysis of clinical data from patients harboring these mutations demonstrated no phenotype/genotype correlation. This study reveals that mutations clustered in a crucial region of ClC‐5 have diverse molecular consequences in patients with Dent disease 1, ranging from altered expression to defects in transport. Abstract : Dent disease type 1 is a renal tubular disorder characterized by low‐molecular‐weight proteinuria, hypercalciuria with nephrocalcinosis or nephrolithiasis, and progressive renal failure. It is associated with mutations in the gene encoding the 2Cl‐/H+ exchanger ClC‐5. Here, we have investigated the consequences of eight previously reported pathogenic missense mutations of ClC‐5 surrounding the 'proton glutamate' (E268), a crucial H+−binding site for the exchanger. We have demonstrated that these mutations have diverse consequences, ranging from altered expression to defects in ion transport. In this later case, we demonstrated that ClC−5 protonation might be altered by disruption of the water pathway of the transporter.